Reversible cross-linking coating and method for conductors
By using a crosslinking composition formed by an ethylene polymer and BiTEMPS methacrylate, the problem of difficult to provide reprocessable crosslinked polyethylene insulating material in the prior art is solved, and a comprehensive improvement in heat resistance, durability and processability of the material in cable applications is achieved.
Patent Information
- Application Number
- CN202380051765.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to provide a reprocessable, reusable or recyclable crosslinked polyethylene insulating material to replace traditional XLPE materials, especially in power cables, where the materials need to have good mechanical and insulating properties.
A crosslinking composition formed of ethylene-based polymer and 2,2,6,6-tetramethyl-4-piperidyl methacrylate disulfide (BiTEMPS) methacrylate is used to reversibly crosslink by heating to a reprocessing temperature to form a reprocessable ethylene-based polymer composition.
The ethylene polymer composition crosslinked at the application temperature is realized to be meltable and reprocessable at typical reprocessing temperatures, with heat resistance and durability while maintaining processability, and is suitable for wire and cable applications.
Smart Images

Figure CN119546648A_ABST
Abstract
Description
Background Art
[0001] Cross-linked polyethylene (XLPE) is the main material for the insulation layer in power cables. For medium and high voltage cable manufacturing, XLPE is usually produced by extruding molten low-density polyethylene (LDPE) together with peroxide onto a metal conductor, and then heating the coated conductor to thermally activate the peroxide and initiate free radical crosslinking of the LDPE. This peroxide-induced crosslinking requires energy-intensive post-extrusion processing equipment. Post-extrusion equipment is required to heat the coated conductor as it emerges from the extrusion die outlet. Post-extrusion equipment is required to cool the coated conductor from the high crosslinking temperature to ambient temperature. In order to remove crosslinking byproducts, post-extrusion equipment is required to degas the coated conductor after the coated conductor has cooled.
[0002] Attempts to replace XLPE with non-crosslinked insulation materials (thereby reducing equipment costs) have failed to provide polyethylene that can meet the mechanical and insulation properties of XLPE due to the high stresses placed on the insulation in the power cable environment. XLPE provides thermomechanical integrity at high temperatures. XPLE is able to withstand mechanical stresses at operating temperatures (which can be as high as 90°C or higher).
[0003] The art recognizes a need for a reprocessable, reusable or otherwise recyclable cross-linked polyethylene insulation material suitable for use in power cable applications. Summary of the invention
[0004] The present disclosure relates to coated conductors. In one embodiment, the coated conductor comprises a conductor and a coating on the conductor. The coating is composed of a crosslinked composition formed from a starting material comprising an ethylene-based polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. This produces a coating composed of a crosslinked composition comprising (i) an ethylene-based polymer and a bond having the following structure (2):
[0005]
[0006]
[0007] The present disclosure provides a method. In one embodiment, the method includes providing a coating from a coated conductor. The coating is composed of a crosslinked composition, the crosslinked composition being composed of (i) an ethylene polymer and (ii) a bond having structure (2)
[0008]
[0009] The coating is formed from starting materials of an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. The method includes heating the coating to a reprocessing temperature and forming the coating into a reprocessable ethylene polymer composition at the reprocessing temperature. The method includes forming the reprocessable ethylene composition into a reprocessable preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked ethylene polymer composition, the recrosslinked ethylene polymer composition composed of (i) an ethylene polymer and (ii) a bond having structure (2).
[0010] definition
[0011] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).
[0012] The numerical range disclosed herein includes all values from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values (e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0013] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0014] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0015] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additive, adjuvant, or compound, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent recitation any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.
[0016] "Conductor" is one or more wires or one or more fibers for conducting heat, light and / or electricity at any voltage (DC voltage, AC voltage or transient voltage). The conductor can be a single wire / fiber or multiple wires / fibers and can be in strand form or in tubular form. Non-limiting examples of suitable conductors include carbon and various metals such as silver, gold, copper and aluminum. The conductor can also be an optical fiber made of glass or plastic. The conductor may be covered or may not be covered in a protective sheath. The conductor may be a single cable or multiple cables tied together (i.e., cable core or core). "Cable" and "power cable" refer to at least one conductor in the sheath. "Wire" refers to a single strand of conductive metal (e.g., copper or aluminum) or a single strand of optical fiber. Typically, a cable is two or more wires or optical fibers that are usually bundled together in a common insulating sheath and / or protective sheath. The individual wires or fibers in the sheath may be bare, covered or insulated. A combined cable may contain both wires and optical fibers. When the cable is a power cable, the cable may be designed for low voltage, medium voltage and / or high voltage applications. When the cable is a communications cable, the cable may be designed for telephone, local area network (LAN) / data, coaxial CATV, coaxial RF cable, or fiber optic cable.
[0017] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), ethylene / α-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or multiple reactor configurations.
[0018] "Ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin interpolymer containing a homogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 The ethylene plastomers / elastomers have a density of 0.854 g / cc to 0.920 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Polyolefin plastomers and ENGAGE TM Polyolefin elastomer (available from The Dow Chemical Company), EXACT TM Plastomers (available from Exxon Mobil Chemical), Tafmer TM α-olefin copolymer (available from Mitsui), Solumer TM Polyolefin Elastomers and Supreme TM Polyolefin elastomer (available from SK Chemicals Co.) and Lucene TM Polyolefin elastomer (available from LG Chem Ltd.).
[0019] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C 10The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM (available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.
[0020] As used herein, the term "linear low density polyethylene" (or "LLDPE") refers to a linear ethylene / α-olefin copolymer containing a heterogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).
[0021] The term "low density polyethylene" (or "LDPE") may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is an ethylene homopolymer and is typically produced by high pressure free radical polymerization (≥100 MPa (e.g., 100 MPa-400 MPa), tubular reactor or autoclave reactor with a free radical initiator). The density of LDPE resins is typically in the range of 0.915 g / cc to less than 0.940 g / cc. LDPE is distinct from LLDPE.
[0022] A "jacket" is the outermost coating on a conductor. When a conductor includes a single coating, the coating may act as both a jacket and an insulator on the conductor.
[0023] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers and propylene-based polymers.
[0024] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.
[0025] "Sheath" is a general term and when used with respect to a cable it includes the insulating covering or layer, protective jacket, and the like.
[0026] Test Method
[0027] density Measured according to ASTM D792, with results reported in g / cc at 25°C.
[0028] Dielectric constantThe dielectric constant was measured according to ASTM D150-22 using an instructive high voltage capacitance bridge at 23°C-130°C and 2000V on a nominal 50 mil board.
[0029] Dissipation Factor Dissipation factor is measured according to ASTM D150-22 using an instructive high voltage capacitance bridge at 23°C-130°C and 2000 V on a nominal 50 mil board. Results are reported in radians.
[0030] Mechanical properties (shear storage modulus and loss modulus (G' and G")) The measurements were performed on an ARES strain-controlled oscillatory shear rheometer equipped with 1-inch diameter parallel plate fixtures at an angle of 10 -1 -10 2 Radians per second (rad / s), strain of 0.25%, temperatures of 130°C and 180°C, nominal plate thickness of 75 mils. Tan δ is the ratio of G" to G'.
[0031] Melt Index (MI or I2) (for ethylene-based polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, wherein the results are reported in grams per 10 minutes (g / 10 min).
[0032] Use the Rubber Process Analyzer (RPA) to Rheological analysis . The rheological properties of the compositions were measured using a rotorless oscillatory shear rheometer, AlphaTechnologies RPA 2000 instrument, according to ASTM D6204 under the following test conditions and exceptions. The sample was placed between two sheets of polyester film for analysis. The rheology was monitored at 180°C, 1.0 rad / s, and 7% strain for 60 minutes during the initial timed test. The elastic torque S' was recorded at the end of the 60-minute (min) crosslinking step. Immediately after 60 minutes at 160°C, a frequency sweep from 0.1 rad / s to 300 rad / s was performed on the same sample at 180°C, 7% strain, followed by a frequency sweep from 0.1 rad / s to 300 rad / s at 190°C, 7% strain, and then a frequency sweep from 0.1 rad / s to 300 rad / s at 230°C, 7% strain. The dynamic complex viscosity, n*, and tan δ were recorded for each frequency sweep. In ASTM D6204, a frequency sweep is performed on unvulcanized rubber before the curing step. In this case, a frequency sweep was performed at 180 °C after the initial cross-linking step to evaluate the reversibility of the cross-linking.
[0033] Volume resistivityMeasured according to ASTM D257-14 using a Hewlett-Packard high resistance meter at 23°C and 500 V on a nominal 50 mil board. Results are reported in ohms / cm. DETAILED DESCRIPTION
[0034] The present disclosure provides a coated conductor. The coated conductor includes a conductor and a coating on the conductor. The coating is composed of a crosslinked composition, which is formed from a starting material comprising an ethylene polymer, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate) and optional additives.
[0035] A. Coated conductor
[0036] The coating is located on the conductor. The coating may be one or more inner layers, such as an insulating layer. The coating may completely or partially cover or otherwise surround or coat the conductor. The coating may be the only component surrounding the conductor. When the coating is the only component surrounding the conductor, the coating may act as a sheath and / or insulator. In one embodiment, the coating is an insulating layer coating the conductor. Alternatively, the coating may be the outermost layer, such as a sheath or outer skin that encases the conductor (and the inner insulating layer).
[0037] In one embodiment, the coating is in direct contact with the conductor. As used herein, the term "direct contact" is a coating configuration in which the coating is positioned immediately adjacent to the conductor, the coating touches the conductor, and no intermediate layers, no intermediate coatings, and / or no intermediate structures exist between the coating and the conductor.
[0038] Alternatively, the coating directly contacts the conductor. As used herein, the term "indirect contact" is a coating configuration in which an intermediate layer, intermediate coating, or intermediate structure is present between the coating and the conductor. Non-limiting examples of suitable intermediate layers, intermediate coatings, and intermediate structures include insulating layers, moisture barriers, buffer tubes, and combinations thereof. Non-limiting examples of suitable insulating layers include foamed insulating layers, thermoplastic insulating layers, cross-linked insulating layers, and combinations thereof. In another embodiment, the coating indirectly contacts the conductor, the coating is indirectly in contact with the insulating layer, or the semiconductive layer surrounds the conductor.
[0039] B. Ethylene polymers
[0040] The coating is formed from a crosslinkable polymer composition (interchangeably referred to as a "starting material") comprising an ethylene polymer. The ethylene polymer may be an ethylene homopolymer, an ethylene / C3-C 10Alpha-olefin copolymers or ethylene C4-C8 alpha-olefin copolymers. The melt index (MI) of the ethylene polymer is 0.1g / 10min to 100g / 10min, or 1g / 10min to 100g / 10min, or 1g / 10min to 50g / 10min, or 1g / 10min to 25g / 10min, or 1g / 10min to 10g / 10min, or 1g / 10min to 5g / 10min. Non-limiting examples of suitable ethylene polymers include high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE) and combinations thereof.
[0041] In one embodiment, the ethylene-based polymer is a LDPE ethylene homopolymer and has one, some or all of the following properties:
[0042] A density of 0.910 g / cc to 0.940 g / cc, or 0.912 g / cc to 0.935 g / cc; and / or
[0043] Melt index (MI) of 0.1 to 100. Non-limiting examples of suitable LDPE include those prepared by autoclave or tubular process technology. A preferred polymer is high pressure low density polyethylene (LDPE). The high pressure process is usually a free radical initiated polymerization carried out in a tubular reactor or a stirred autoclave. In a stirred autoclave, the pressure is in the range of 10,000 psi to 30,000 psi (70 kPa to 210 kPa), and the temperature is in the range of 175°C to 250°C; in a tubular reactor, the pressure is in the range of 25,000 psi to 45,000 psi (170 kPa to 310 kPa), and the temperature is in the range of 200°C to 350°C.
[0044] C. Free Radical Initiator
[0045] The crosslinkable polymer composition forming the coating comprises a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.
[0046] In one embodiment, the free radical initiator is dicumyl peroxide.
[0047] In some embodiments, the crosslinkable polymer composition forming the coating comprises a cure package comprising a free radical initiator and an optional auxiliary agent. Examples of the free radical initiator include diisopropyl peroxide; bis(α-tert-butylperoxyisopropyl)benzene; isopropyl cumyl tert-butyl peroxide; tert-butyl cumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3; 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane; isopropyl cumyl cumyl peroxide; di(isopropylcumyl) peroxide; and mixtures of two or more such initiators. The amount of free radical initiator used is typically 0.1% to 3% by weight, more typically 0.5% to 3% by weight, and even more typically 1% to 2.5% by weight, based on the weight of the composition. Various curing aids (as well as accelerators or retarders) can be used in combination with peroxide initiators, and these peroxide initiators include triallyl isocyanurate; ethoxylated bisphenol A dimethacrylate; alpha-methylstyrene dimer (AMSD); and other active aids as described in U.S. Pat. Nos. 5,346,961 and 4,018,852. If used, the amount of the adjuvant is typically greater than 0 (e.g., 0.01 wt %) to 3 wt %, more typically 0.1 wt % to 0.5 wt %, and even more typically 0.2 wt % to 0.4 wt %, based on the weight of the composition.
[0048] D.BiTEMPS Methacrylate
[0049] The crosslinkable polymer composition forming the coating comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.
[0050] Structure 1
[0051]
[0052] In one embodiment, the crosslinkable polymer composition comprises:
[0053] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of an ethylene polymer;
[0054] 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt %, 0.1 wt % to 3.0 wt %, or 0.1 wt % to 1.5 wt %, or 0.5 wt % to 1.5 wt % of a free radical initiator which is an organic peroxide (e.g., dicumyl peroxide); and
[0055] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 2 wt % to 20 wt %, or 2 wt % to 10 wt % BiTEMPS methacrylate. It is understood that the aggregate of the vinyl polymer, free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.
[0056] The crosslinked composition of the conductor coating is formed from a crosslinkable polymer composition. The crosslinkable polymer composition is melt blended at a temperature of 100°C to 250°C, or 120°C to 210°C, or 140°C to 210°C, or 140°C to 190°C to initiate a crosslinking reaction and form a crosslinked composition. In one embodiment, the crosslinked composition comprises an ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The crosslinked composition contains a disulfide bond formed by BiTEMPS methacrylate through a crosslinking reaction, and the disulfide bond has the following structure 2.
[0057] Structure 2
[0058]
[0059] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized ethylene (and optional comonomers) of the ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having an MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein. Non-limiting examples of suitable ethylene polymers include ethylene / α-olefin interpolymers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and combinations thereof.
[0060] In one embodiment, the ethylene polymer is a virgin ethylene polymer. As used herein, a "virgin ethylene polymer" is an ethylene polymer that has not been subjected to a crosslinking reaction. In other words, the term "virgin ethylene polymer" refers to the ethylene polymer that was present in the crosslinked composition before the ethylene polymer was crosslinked with the BiTEMPS methacrylate. The virgin ethylene polymer is the ethylene polymer before crosslinking, and the crosslinked composition comprises the same ethylene polymer that is virgin but now crosslinked with the BiTEMPS methacrylate. In this way, the virgin ethylene polymer is used as a benchmark for evaluating the properties of the crosslinked composition. The crosslinked composition has
[0061] (i) a shear storage modulus value G' at 130°C that is greater than the storage modulus value G' of the native ethylene polymer at 130°C;
[0062] (ii) a tan δ value at 130°C that is less than the tan δ value of the native ethylene polymer at 130°C,
[0063] and forming a coating as disclosed above.
[0064] In one embodiment, the crosslinked composition comprises 80 wt % to 97 wt % of the ethylene polymer and 2 wt % to 20 wt % of the BiTEMPS methacrylate, the aggregate of the ethylene polymer and the BiTEMPS methacrylate (and optional additives) totaling 100 wt % of the crosslinked composition. The crosslinked composition in the coating has
[0065] (i) a shear storage modulus value G' greater than 100 kPa at 130°C and 100 rad / s;
[0066] (ii) a shear storage modulus value G' at 130°C and 0.1 rad / s greater than 10 kPa; and
[0067] (iii) a tan δ value of less than 0.60 at 130°C.
[0068] E. Blend Components
[0069] In one embodiment, the crosslinkable polymer composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include ethylene-vinyl acetate (EVA), polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.
[0070] Other examples of suitable blending components include functionalized ethylene polymers, including ethylene polymers composed of (i) ethylene monomers, (ii) comonomers containing heteroatoms, and (iii) optional terionomers (which may or may not contain heteroatoms). Non-limiting examples of comonomers having heteroatoms include carbon monoxide, carboxylic acids, esters, alkyl acrylates having 1 to 30 carbon atoms, methacrylates having 1 to 30 carbon atoms, vinyl siloxanes having 1 to 16 carbon atoms and halogens. Non-limiting examples of suitable functionalized vinyl polymers include ethylene / carboxylic acid copolymers and partially neutralized ionomers with metal salts derived therefrom, ethylene / acrylic acid copolymers (EAA), ethylene / methacrylic acid copolymers (EMAA), ethylene / vinyl (trimethoxy) silane copolymers (EVTMS), ethylene / vinyl acetate copolymers (EVA), ethylene / methyl acrylate (EMA), ethylene / ethyl acrylate copolymers (EEA), ethylene / butyl acrylate copolymers (EBA), ethylene / carbon monoxide (ECO), ethylene / glycidyl methacrylate (E / GMA), ethylene / methyl methacrylate copolymers, ethylene / butyl methacrylate copolymers, ethylene / octadecyl acrylate copolymers, ethylene / octadecyl methacrylate copolymers, ethylene / octyl acrylate copolymers, ethylene / 2-ethylhexyl acrylate copolymers, ethylene / dodecyl acrylate copolymers, polyvinyl dichloride (PVCD), ethylene / maleic anhydride copolymers (EMAH), polyvinyl chloride (PVC), and combinations thereof. Additional non-limiting examples of terpolymers include ethylene / carboxylic acid / acrylate terpolymers and partially neutralized ionomers with metal salts derived therefrom, ethylene / methyl acrylate / vinyl (trimethoxy) silane terpolymers (EMAVTMS), ethylene / ethyl acrylate / vinyl (trimethoxy) silane terpolymers (EEAVTMS), ethylene / butyl acrylate / vinyl (trimethoxy) silane terpolymers (EBAVTMS), ethylene / methyl acrylate / glycidyl methacrylate (EMAGMA), ethylene / butyl acrylate / glycidyl methacrylate (EBAGMA), ethylene / vinyl acetate / maleic anhydride terpolymers (EEAMAH), and ethylene ethyl acrylate / maleic anhydride (EEAMAH) terpolymers.
[0071] In one embodiment, the polyolefin is a homopolymer such as polyethylene, polypropylene, polybutene, polypentene-1, poly-3-methylbutene-1, poly-4-methylpentene-1, polyisoprene, polybutadiene, poly-1,5-hexadiene, polyhexene-1, polyoctene-1, and polydecene-1.
[0072] Non-limiting examples of polyethylenes suitable as blend components (other than ethylene polymers crosslinked with BITEMPS methacrylate) include ultra low density polyethylene (ULDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high molecular weight high density polyethylene (HMW-HDPE), ultra high molecular weight polyethylene (UHMW-PE), and combinations thereof. Non-limiting examples of polypropylenes include low density polypropylene (LDPP), high density polypropylene (HDPP), high melt strength polypropylene (HMS-PP), and combinations thereof. In one embodiment, the blend component is high melt strength polypropylene (HMS-PP), low density polyethylene (LDPE), or combinations thereof.
[0073] F. Additives
[0074] The crosslinkable polymer composition and / or the crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of the additive may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition. Examples of fillers include, but are not limited to, clays, precipitated silica and silicates, fumed silica, calcium carbonate, ground minerals, and carbon black, with typical arithmetic mean particle sizes greater than 15 nanometers.
[0075] BiTEMPS methacrylate is a "dynamic crosslinker". The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network with ethylene polymers through disulfide bonds between the chains of the ethylene polymers (in the presence of a free radical initiator), thereby forming a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature", thereby allowing chain movement and exchange, which is a temperature of 160°C to 230°C, or 160°C to 200°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.
[0076] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables crosslinking to break and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking and manufacturing into new articles can be repeated.
[0077] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing). For reprocessable, crosslinked ethylene polymer compositions, the ratio of the viscosity after reprocessing to the viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.
[0078] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.
[0079] The coating can be formed by melt blending. "Melt blending" is a process in which at least two components (i.e., components of the crosslinkable polymer composition: ethylene polymer, peroxide, BiTEMPS methacrylate, and optional additives) are combined or otherwise mixed together, and at least one component (the ethylene polymer) is in a molten state. Melt blending can be accomplished by batch mixing, extrusion blending, extrusion molding, and any combination thereof.
[0080] In one embodiment, the crosslinkable polymer composition is extruded on the conductor to form a coating. The extruder has a crosshead die that provides the desired layer (wall or coating) thickness. A non-limiting example of an extruder that can be used is a single screw type modified with a crosshead die, a cooling pass, and a continuous winding device. A typical single screw type extruder can be described as an extruder having a hopper at its upstream end and a die at its downstream end. The hopper feeds into a barrel equipped with a screw. At the downstream end, between the end of the screw and the die, there is a filter assembly and a circuit breaker plate. It is believed that the screw portion of the extruder is divided into three sections, namely a feeding section, a compression section, and a metering section, as well as multiple heating zones from the rear heating zone to the front heating zone, wherein these multiple sections extend from upstream to downstream. The aspect ratio of the barrel is 16:1 to 30:1. A grooved barrel extruder or a twin screw extruder can also be used for the core coating process. The extrusion process can be carried out at a temperature in the range of 80°C, or 100°C, or 120°C, or 140°C, or 160°C, or 180°C, or 200°C, or 220°C, or 240°C, or 260°C. The crosshead die distributes the melt-blended crosslinkable polymer composition in the flow channel so that the molten crosslinkable polymer composition exits and is applied to the conductor at a uniform rate. In this way, blending (melt blending) and extrusion are carried out in the same single extruder. The conductor passes through the center of the crosshead, and as the conductor exits, a uniform layer of the molten crosslinkable polymer composition is applied in the circumferential direction using pressure or semi-pressure of tube-on cooling.
[0081] One or more layers of the crosslinkable polymer composition can be applied as corresponding one or more coatings using a multi-crosshead. The conductor (having the molten crosslinkable polymer composition thereon, hereinafter interchangeably referred to as the "core") continues to move through the molding channel to the outside of the die, and the core is then cooled to harden the crosslinkable polymer composition (optionally by passing the core through a water tank) to prevent deformation of the crosslinkable polymer composition applied as a coating on the take-up reel, thereby producing a coated conductor, the coating being composed of the crosslinked composition.
[0082] In one embodiment, the coating is an insulating layer on a conductor and the coating consists solely of a crosslinked composition, and the crosslinked composition comprises, consists essentially of, or consists of:
[0083] (i) 80 wt % to 99.9 wt %, or 83 wt % to 97 wt % of an ethylene polymer;
[0084] (ii) a bond of Structure 2 (formed by 1 wt % to 15 wt %, or 3 wt % BiTEMPS methacrylate);
[0085] (iii) 0 wt %, or 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt % of a free radical initiator;
[0086] (iv) 0 wt%, or 0.1 wt% to 1.0 wt%, or 0.1 wt% to 0.5 wt% of additives,
[0087] The aggregate of the ethylenic polymer and the bonds of Structure 2 (formed from BiTEMPS methacrylate) (and optional additives) total 100 wt % of the crosslinked foam composition.
[0088] In one embodiment, the coated conductor comprises a coating consisting solely of a crosslinked composition comprising, consisting essentially of, or consisting of:
[0089] (i) 80 wt% to 99.9 wt%, or 83 wt% to 97 wt% of the ethylene-based polymer is LDPE ethylene homopolymer having
[0090] (a) a density of 0.910 g / cc to 0.940 g / cc; and / or
[0091] (b) a melt index of 0.1 g / 10 min to 100 g / 10 min,
[0092] (ii) a bond of Structure 2 (formed from 0.5 wt % to 15 wt %, or 2.0 wt % to 15 wt % BiTEMPS methacrylate);
[0093] (iii) 0% by weight, or 0.1% by weight to 0.5% by weight of an additive as an antioxidant,
[0094] and
[0095] The cross-linked composition has one, some or all of the following properties:
[0096] (iv) 10 at 23°C 16 ohm / cm to 10 20 Outgassing volume resistivity in ohm / cm, and / or
[0097] (v) 10 at 23°C 15 ohm / cm to 10 20ohm / cm, and / or (vi) a dielectric constant of 2.20 to 2.70 at 23°C, and / or
[0098] (vii) a dielectric constant of 1.80 to 2.10 at 110°C, and / or
[0099] (viii) a loss factor of 0.0001 rad to 0.01 rad at 23°C and 60 Hz, and / or
[0100] (ix) a loss factor of 0.0001 rad to 0.01 rad at 110°C and 60 Hz, and / or
[0101] (x) 10 at 130°C and 100 rad / s 5 Pa to 10 7 Pa's G', and / or
[0102] (xi) 10 at 130°C and 100 rad / s 4 Pa to 10 7 Pa's G', and / or
[0103] (xii) tan δ of 0 to 0.6 at 130°C.
[0104] In one embodiment, the coating contains carbon black and the coating is a semiconducting layer on a conductor.
[0105] In one embodiment, the coated conductor is selected from fiber optic cables, communication cables (such as telephone cables, local area network (LAN) cables, or small form-factor pluggable (SFP) cables), power cables, wiring for consumer electronic devices, power charging cables for cellular phones and / or computers, computer data cables, power cords, appliance wiring materials, in-house wiring materials, consumer electronic accessory wires, and any combination thereof.
[0106] A coating composed of a crosslinked composition may comprise two or more embodiments disclosed herein.
[0107] G. Methods
[0108] The present disclosure provides a method. In one embodiment, the method includes providing a coating from a coated conductor. The coating is composed of a cross-linked composition, which is composed of: (i) an ethylene polymer, (ii) a bond of structure 2 (formed by 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate)), and (iii) an optional additive. The method includes heating the coating to a reprocessing temperature. The method includes forming the coating into a reprocessable ethylene polymer composition at the reprocessing temperature. The method includes forming the reprocessable ethylene composition into a reprocessed preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a re-crosslinked ethylene polymer composition, which is composed of: (i) an ethylene polymer and (ii) a bond of structure 2 (formed by BiTEMPS methacrylate).
[0109] In one embodiment, the method includes removing the coating from the coated conductor. The removing step is performed prior to heating to the reprocessing temperature.
[0110] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.
[0111] Non-limiting examples of suitable second articles for the cross-linked / re-cross-linked ethylene polymer (having structure (2) formed from BiTEMPS methacrylate) composition of the present invention include coatings on conductors, three-dimensional annular articles; elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather strips; lid linings; flooring; and combinations thereof.
[0112] Applicants have discovered that coatings consisting of crosslinked compositions of ethylene polymers and bonds of structure 2 (formed by BiTEMPS methacrylate) (and optional additives) are capable of undergoing reversible crosslinking at reprocessing temperatures. Reversible crosslinking is achieved by forming a coating from a crosslinkable polymer composition consisting of an ethylene polymer, a peroxide, BITEMPS methacrylate (and optional additives). The composition of the present invention forms a coating for a conductor consisting of a crosslinked composition, wherein the crosslinked composition crosslinks at application use temperatures (ambient temperatures up to 130°C), but can be melt reprocessed at typical reprocessing temperatures (about 160°C-250°C). Thus, the present invention provides the benefits of a coating for a conductor for wire and cable applications that has heat resistance and durability while maintaining (re)processability at typical extrusion temperatures.
[0113] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.
[0114] 1. Materials
[0115] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.
[0116] Table 1 - Materials used in the Inventive Examples ("IE") and Comparative Samples ("CS")
[0117]
[0118] 2. Synthesis of BITEMPS Methacrylate
[0119] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (about 90 mL, provided by Sigma-Aldrich, dried over molecular sieves for 48 hours before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hours to obtain BiTEMPS methacrylate as shown in the following structure 1.
[0120] Structure 1
[0121]
[0122] 3. Recipe
[0123] LDPE #1, dicumyl peroxide, BiTEMPS methacrylate, and antioxidant A were combined (in the amounts shown in Table 2 below) and batch mixed at 120°C to form a crosslinkable polymer composition. The crosslinkable polymer composition was heated on an RPA at 180°C for 30 minutes to initiate the crosslinking reaction. The characteristics of the crosslinking reaction are provided in Table 2A.
[0124] Plates were also made from the crosslinkable polymer composition by pressing about 35 g portions in a Wabash press. For CS1, the pellets were pressed at 120°C and 500 psi for 5 minutes, cut into sheets, restacked, and pressed again at 120°C and 500 psi for 5 minutes, then at 2500 psi for 5 minutes, and then finally at 180°C and 2500 psi for 15 minutes to cure the plate. For all other embodiments, the single piece was pressed at 180°C and 500 psi for 5 minutes, followed by 2500 psi for 15 minutes. For electrical testing, the plates were nominally 50 mils, while for mechanical testing, the plates were nominally 75 mils, and the plates were reformed from the initial 50 mil plates (except for CS1, where two separate plates were prepared). The electrical and mechanical data are in Tables 2B and 2C below, respectively. CS1 and IE1 were degassed after sample preparation, but CS2 and IE2-4 were not degassed.
[0125] Table 2A - Crosslinked Composition and Properties of Coatings
[0126]
[0127] Table 2B: Crosslinked compositions and electrical properties of the coatings. Samples CS1 and IE1 degassed, while the other samples CS2 and IE2-4 did not degas.
[0128] Table 2B
[0129]
[0130]
[0131]
[0132] As shown in Table 2B, Table 3A and Table 3B, the electrical properties of the embodiments of the present invention and the comparative samples are similar. The degassed volume resistivity (the higher the better) of the embodiment of the present invention 1 is higher than the degassed volume resistivity of the comparative sample 1, although both are very high and of the same order of magnitude. For the other embodiments, they are not degassed, so all of their resistivities are lower. Nevertheless, the non-degassed volume resistivities of the embodiments of the present invention 2-4 are higher than the volume resistivities of the comparative sample 2.
[0133] The dielectric constant (lower the better) and dissipation factor (lower the better) of Inventive Examples 1-4 are each very low and acceptable for wire and cable applications. Notably, the dielectric constant and dissipation factor of IE 1-4 are similar or substantially similar to the dielectric constant and dissipation factor values of CS 1-2. However, the coatings of each of IE 1-4 are reprocessable, while the coatings of each of CS-1 and CS-2 are permanently crosslinked and are not reprocessable, as shown in the mechanical data.
[0134] Specifically, all tan δ values for CS-1 and CS-2 are well below unity (well below 1), indicating permanently crosslinked materials, while most tan δ values for Inventive Examples 1-3 are well below unity, except for those at 180°C and low frequencies, indicating a transition to a flowable material. Inventive Example 4 has a higher crosslink density and therefore has a low tan δ under all conditions tested; however, these measurements were still made on pressed plaques, indicating its ability to be reprocessed.
[0135] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A coated conductor, comprising: conductor; and A coating on the conductor, the coating being composed of a cross-linked composition formed from a starting material comprising: Ethylene polymers; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).
2. The coated conductor of claim 1, wherein the crosslinking composition comprises a bond of structure 2.
3. The coated conductor of any one of claims 1 to 2, wherein the crosslinking composition is formed from a starting material comprising: 80 to 99 weight percent of an ethylene-based polymer having a melt index of 0.1 to 100 g / 10 min; and 20 wt % to 1 wt % of said BiTEMPS methacrylate.
4. The coated conductor of any one of claims 1 to 3, wherein the ethylene-based polymer is low density polyethylene (LDPE).
5. The coated conductor of claim 4, wherein the LDPE has a property selected from the group consisting of: (i) a density of 0.910 g / cc to 0.940 g / cc, (ii) a melt index of 0.1 g / 10 min to 100 g / 10 min, and (iii) combinations thereof.
6. The coated conductor according to any one of claims 1 to 5, comprising an additive selected from the group consisting of carbon black, antioxidants, stabilizers, processing aids, and combinations thereof.
7. A coated conductor according to any one of claims 1 to 6, wherein the crosslinking composition is formed from a starting material comprising: (i) 80 wt % to 99 wt % of the ethylene polymer; (ii) 1 wt % to 15 wt % of said BiTEMPS methacrylate; (iii) 0 to 0.5 wt% of a free radical initiator.
8. The coated conductor of claim 7, wherein the crosslinking composition has a property selected from the group consisting of: (i) 10 at 23°C 16 ohm / cm to 10 20 Outgassing volume resistivity in ohm / cm, (ii) 10 at 23°C 15 ohm / cm to 10 20 Undegassed volume resistivity in ohm / cm, (iii) a dielectric constant of 2.20 to 2.70 at 23°C, (iv) a dielectric constant of 1.80 to 2.10 at 110°C, (v) a loss factor of 0.0001 rad to 0.01 rad at 23°C and 60 Hz, (vi) a loss factor of 0.0001 rad to 0.01 rad at 110°C and 60 Hz, and / or (vii) a loss factor of 10 at 130°C and 100 rad / s. 5 Pa to 10 7 Pa's G', (viii) 10 at 130°C and 100 rad / s 4 Pa to 10 7 Pa's G', (ix) a tan delta of 0 to 0.6 at 130°C, and (x) A combination thereof.
9. A coated conductor, comprising: conductor; and The coating on the conductor is composed of a cross-linking composition, and the cross-linking composition comprises: Ethylene polymers; and A bond with structure (2) 10. A method comprising: A coating is provided by coating the conductor, the coating being composed of a cross-linked composition, the cross-linked composition being composed of: (i) ethylene polymers, and (ii) A bond having structure (2) heating the coating to a reprocessing temperature; forming the coating into a reprocessable ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene composition into a reprocessable preform at the reprocessing temperature; as well as The reprocessed preform is cooled to below the reprocessing temperature and forms a second article composed of a recrosslinked ethylene polymer composition, wherein the recrosslinked ethylene polymer composition is composed of (i) the ethylene polymer and (ii) bonds having the structure (2).
11. The method according to claim 10, comprising: The coating is removed from the coated conductor.
Citation Information
Patent Citations
Composition with triallyl compounds and process for avoiding scorching of ethylene polymer composition
US4018852A
Process for crosslinking
US5346961A